Reliability of 2-dimensional video assessment of frontal-plane dynamic knee valgus during common athletic screening tasks - Munro, Allan; Herrington, Lee; Carolan, Michael (Journal of sport rehabilitation, 2012)
Two-dimensional (2D) video analysis of frontal-plane dynamic knee valgus during common athletic screening tasks has been purported to identify individuals who may be at high risk of suffering knee injuries such as anterior cruciate ligament tear or patellofemoral pain syndrome. Although the validity of 2D video analysis has been studied, the associated reliability and measurement error have not. To assess the reliability and associated measurement error of a 2D video analysis of lower limb dynamic valgus. Reliability study. 20 recreationally active university students (10 women age 21.5 ± 2.3 y, height 170.1 ± 6.1 cm, weight 66.2 ± 10.2 kg, and 10 men age 22.6 ± 3.1 y, height 177.9 ± 6.0 cm, weight 75.8 ± 7.9 kg). Within-day and between-days reliability and measurement-error values of 2D frontal-plane projection angle (FPPA) during common screening tasks. Participants performed single-leg squat and drop jump and single-leg landings from a standard 28-cm step with standard 2D digital video camera assessment. Women demonstrated significantly higher FPPA in all tests except the left single-leg squat. Within-day ICCs showed good reliability and ranged from .59 to .88, and between-days ICCs were good to excellent, ranging from .72 to .91. Standard error of measurement and smallest detectable difference values ranged from 2.72° to 3.01° and 7.54° to 8.93°, respectively. 2D FPPA has previously been shown to be valid and has now also been shown to be a reliable measure of lower extremity dynamic knee valgus. Using the measurement error values presented along with previously published normative data, clinicians can now make informed judgments about individual performance and changes in performance resulting from interventions.